Genistein supplementation alleviates the deterioration in performance and antioxidant status of Japanese quail associated with heat stress. - Şahin, Kazım; Onderci, M; Gursu, MF; Şahin, Nurhan; Doerge, D; Sarkar, F; Küçük, Ömer (Amer Inst Nutrition, 2004)
[Abstract Not Available]
5th International Symposium on the Role of Soy in Preventing and Treating Chronic Disease -- SEP 21-24, 2003 -- Orlando, FL